8 Rapid cycle improvement in the hot zone. (2nd December 2020) - Douglas, Elizabeth; Fraser, Kristina
Abstract : Background: UNTHSC opened Fort Worth's first drive-through coronavirus testing site which functioned as both a community service and an opportunity for health professional students to learn rapid cycle improvement. Nasopharyngeal swabs were administered through vehicle windows in what was referred to as 'the hot zone.' Throughout 12 weeks many changes were made to the hot zone, including installing a tent, adding a second lane, improving hot zone staff training, and staggering opening times. Objectives: To ensure safe, efficient, and effective SARSCoV-2 testing for patients and staff. Methods: Total tests and times per test were recorded. Time in PPE was calculated from the time PPE was donned to average time doffed. Positive test count was used as a metric for pathogen exposure. Total cases among staff were also recorded along with near misses, incidents, and good catches as discussed in daily team debrief. Training was standardized and videos were created for hot zone and safety officer staff. Results: The site was open from March to June. With the tent, the accidental hot zone entry rate dropped from average of almost once per day to only once in 11 weeks. There were only 3 heat related incidents intercepted and 0 cases of COVID-19 among the 400 students and faculty. 8 safety incidents occurred. An average of 4 good catches or incidents prevented were counted per week. With staggering, time in full PPE was reduced from 165 minutes to 120 minutes. The record for most tests administered per shift increased from 55 for one lane to 112 for two lanes (figure 1 ). Conclusions: Lessons learned here about heat safety, pathogen safety, and hot zone training can be applied to all drive thru testing sites. With this ongoing pandemic, it is wise to look for ways to improve test sites as well as potential vaccination sites.